Analisis Common Size untuk Menganalisa Kinerja Keuangan PT. Industri Jamu dan Farmasi Sido Muncul Tbk - Az-Zahro, Shofia; Wirman, Wirman (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the financial performance of PT. Industri Jamu dan Farmasi Sido Muncul Tbk during the 2021–2023 period using the common size analysis method. The data used are secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange. The results indicate that the company's financial structure is relatively stable, with a high proportion of current assets and a capital structure dominated by equity, reflecting good liquidity and solvency levels. However, there is a consistent decline in net profit each year due to increasing operating expenses, even though gross profit remains relatively stable. This suggests a decrease in the company’s operational efficiency. Therefore, managerial efforts are needed to manage operating expenses and improve efficiency in order to maintain and enhance the company’s financial performance in the future.